Colletotrichum truncatum and C. fructicola causing anthracnose on chilli in Karnataka state of India - K.V. PAVANI, C.S. CHETHANA, P. CHOWDAPPA* and (Indian Phytopathology, 2015)
Chilli is an important spice as well as vegetable crop in India. Anthracnose is one of the most devastating diseases wherever chillies are grown under warm and wet season. The disease appears as sunken necrotic lesions with concentric rings of acervuli on fruit. Colletotrichum species responsible for severe outbreaks of anthracnose on chillies in Karnataka state of India are reported. Forty nine isolates recovered from major chilli production areas of Karnataka state were characterized based on morphological and multilocus gene phylogeny using partial ITS, ACT, CHS-1, GAPDH, CYLH3, TUB2, GS and ApMat genes. The results showed the presence of two species, C. truncatum (37 isolates) and C. fructicola (12 isolates). Pathogenecity assays of the two species were confirmed on ‘chilli cv Arka Lohith’. Thus, the results of this study can be utilized for devising disease management strategies and for the development of disease resistant varieties for use in commercial production of chilli in India.